2003
DOI: 10.1016/s0266-7681(03)00103-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Hand Fractures

Abstract: A retrospective survey of the medical charts of all 36,518 patients attending the Accident and Emergency Department of the VU University Medical Centre, in Amsterdam, from January 1 to December 31, 1996 was performed. Of these, 4303 sustained one or more fractures, and hand fractures accounted for 19% of all fractures. Patients with hand fractures were typically men aged between 15 and 35 years. The right hand was involved as often as the left. Most of the hand fractures involved the metacarpals but, as a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
115
3
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 15 publications
18
115
3
10
Order By: Relevance
“…This is in accordance with other studies [1,2,5,9]. In our material, the 5 th finger in general and the 5 th metacarpal bone in particular was more prone to injury than the other fingers, a result also reported by others [2--4, 12].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in accordance with other studies [1,2,5,9]. In our material, the 5 th finger in general and the 5 th metacarpal bone in particular was more prone to injury than the other fingers, a result also reported by others [2--4, 12].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown higher incidence of hand fractures among males than females between the age of 10 and 60 years [2,4,5,8]. Hand fractures are most common among people between 10 and 40 years of age [2,4,8].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…'nın (11) çalışmasın-da, sol tarafın kırık üstünlüğü bulunmuştur (%51,2) hatta bu oran bazı çalışmalarda %90'lara çıkmaktadır ve yazarlar tarafından da belirtildiği gibi erkeklerde el bilek travmalarının sıklığı kadınlardan daha fazla olarak izlenmektedir (%60,4) (12,13) . Ancak, çalışmalar el-bilek kırıklarını kadın ve erkeklerde eşit olarak bildirmektedirler (11) . Bizim çalışmamızda ise, okult kı-rıklar da erkeklerde daha sık olarak saptandı (%63,6).…”
Section: Discussionunclassified